Screening of vaginal candido sis during the prevention of uterine cervix cancer - Cavalcante, Vânia L.N.; Miranda, Aldine T.; Portugal, Glenda M.P. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: vaginal candidosis is one of the most prevalent infection of the lower genital tract around the world. Lately a huge increase in incidence accounted for ranking this disease as the second more frequent vaginal infection in Brazil. These reasons led some authors to indicate the screening of vaginal discharge in gynecology clinics. Objective: the aim of this study was to observe the prevalence of vaginal candidosis in women submitted to uterine cervical cancer’s screening by comparing the results obtained in Papanicolaou smears and in bacterioscopy (Gramand directmicroscopic examination). Method: the sample comprises 145 women, aged 15 to 45 years old, that in the period of January to May 2002 underwent cervical cancer screening at “Unidade Materno-Infantil” of Para State University. Vaginal candidosis diagnosis was based on the presence of Candida sp and vaginal discharge associated to the absence of Trichomonas vaginalisand clue cells. Results:a global prevalence of 35% wasobserved. Bacterioscopic examination detected 74,8% and Papanicolaou 22,5% of Candida sp in women with vaginal discharge. Conclusion: thoseresults drawn the conclusion that vaginal candidosis is a prevalent affection being the bacterioscopy, in this case, the most sensitive laboratorymethod for detection of the yeast.